2020
DOI: 10.1038/s41467-020-16053-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances motor skill learning by neurotransmitter switching in the adult midbrain

Abstract: Physical exercise promotes motor skill learning in normal individuals and those with neurological disorders but its mechanism of action is unclear. We find that one week of voluntary wheel running enhances the acquisition of motor skills in normal adult mice. One week of running also induces switching from ACh to GABA expression in neurons in the caudal pedunculopontine nucleus (cPPN). Consistent with regulation of motor skills, we show that the switching neurons make projections to the substantia nigra (SN), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 57 publications
(73 reference statements)
1
45
0
Order By: Relevance
“…The observation of the relatively late differentiation of Ia-PNs led us to investigate whether the identity of Ia-PN subtypes remains versatile in adult life following changes in sensorimotor activity. To test this, we used motor skill learning that has been intensely studied in the realm of neuroplasticity 34 36 . More specifically, we assessed the composition of Ia-PN subtypes in DRG of wild-type mice with access to free-wheel running for 4 weeks, which is known to induce experience-dependent plasticity in the central nervous system 36 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of the relatively late differentiation of Ia-PNs led us to investigate whether the identity of Ia-PN subtypes remains versatile in adult life following changes in sensorimotor activity. To test this, we used motor skill learning that has been intensely studied in the realm of neuroplasticity 34 36 . More specifically, we assessed the composition of Ia-PN subtypes in DRG of wild-type mice with access to free-wheel running for 4 weeks, which is known to induce experience-dependent plasticity in the central nervous system 36 38 .…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we used motor skill learning that has been intensely studied in the realm of neuroplasticity 34 36 . More specifically, we assessed the composition of Ia-PN subtypes in DRG of wild-type mice with access to free-wheel running for 4 weeks, which is known to induce experience-dependent plasticity in the central nervous system 36 38 . During the entire training period, running (Run) and sedentary (Sed) mice were single housed in enhanced environment: large rat cage, wooden sticks, nest and free access to a running wheel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ChAT + neurons in the peripheral and central nervous systems may become GABAergic or glutamatergic. It is suggested that cholinergic phenotypic plasticity is necessary for fine-tuning of movement and procedural learning across the lifespan as well as transitioning between physiological states like the "fight-or-flight" response and rest (Li & Spitzer, 2020;Spitzer, 2017). It is possible that AE during the brain growth spurt leads to a neurotransmitter switch, altering the phenotype of neurons in NBM in adulthood.…”
Section: Ae During the Brain Growth Spurt Reduces Cholinergic Neuromentioning
confidence: 99%
“…Interestingly, our results suggest that cholinergic neurons in NBM are resistant to phenotypic change resulting from either behavioral intervention tested in adolescence-adulthood. Specific cholinergic nuclei are more amenable to phenotypic alteration in adolescenceadulthood than others, namely those in the midbrain, brainstem, and septum (Hall & Savage, 2016;Li & Spitzer, 2020;Spitzer, 2017). Phenotypic plasticity of cholinergic neurons in NBM is under explored.…”
Section: Ae During the Brain Growth Spurt Reduces Cholinergic Neuromentioning
confidence: 99%
“…Bar-graphs to the right are distribution histograms of the phases of inspiratory bursts and the same reference limb for all n events from 7 animals. a paradigm known to enhance locomotor skills (Chen et al, 2019;Li and Spitzer, 2020). Animals were then implanted with EMG electrodes and challenged to treadmill running at the 3 speeds on a level or inclined treadmill as well as to the air puff driven gallop as performed above.…”
Section: (C-f)mentioning
confidence: 99%